2018
DOI: 10.1097/ccm.0000000000002796
|View full text |Cite
|
Sign up to set email alerts
|

Renal Replacement Therapy Modality in the ICU and Renal Recovery at Hospital Discharge*

Abstract: In this large retrospective study, intermittent hemodialysis as an initial modality was associated with lower renal recovery at hospital discharge among patients with acute kidney injury, although the difference seems somewhat clinically limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
5
31
0
1
Order By: Relevance
“…Table indicated the characteristics of all included studies. Lastly, the study included 11 articles for comparison between AKI patients treated with CRRT and IHD, 10‐12,14‐21 eight articles for comparison between AKI patients treated with CRRT and SLED, 8,9,22‐26 and three articles 27‐29 for comparison between AKI patients treated with CRRT and IRRT (which kind of IRRT was not clear), respectively. For comparison between AKI patients treated with CRRT and IHD, these studies included totally 42 079 AKI patients given CRRT and 19 154 patients given IHD.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Table indicated the characteristics of all included studies. Lastly, the study included 11 articles for comparison between AKI patients treated with CRRT and IHD, 10‐12,14‐21 eight articles for comparison between AKI patients treated with CRRT and SLED, 8,9,22‐26 and three articles 27‐29 for comparison between AKI patients treated with CRRT and IRRT (which kind of IRRT was not clear), respectively. For comparison between AKI patients treated with CRRT and IHD, these studies included totally 42 079 AKI patients given CRRT and 19 154 patients given IHD.…”
Section: Resultsmentioning
confidence: 99%
“…Bonnassieux et al showed lower renal recovery and higher in‐ICU mortality in AKI patients treated with CRRT, compared to those treated with IHD 20 . AKI patients treated with CRRT showed a higher rate of baseline vasopressor use compared to AKI patients treated with IHD 20 . The study is a RCT study with large cohort (40 905 AKI patients treated with CRRT vs 17 730 AKI patients treated with IHD) 20 .…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations